2020
DOI: 10.1186/s12909-020-02331-x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between learner engagement and teaching effectiveness: a novel assessment of student engagement in continuing medical education

Abstract: Background Continuing medical education (CME) often uses passive educational models including lectures. However, numerous studies have questioned the effectiveness of these less engaging educational strategies. Studies outside of CME suggest that engaged learning is associated with improved educational outcomes. However, measuring participants’ engagement can be challenging. We developed and determined the validity evidence for a novel instrument to assess learner engagement in CME. Methods We conducted a cr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 33 publications
2
45
0
1
Order By: Relevance
“…21 As learner engagement has been strongly associated with teaching effectiveness, it is key for educators to maximize engagement with the virtual platform. 22 This work has limitations. Our response rate of 13% is lower than desirable, and increases the risk of unit non-response bias i.e.…”
Section: Discussionmentioning
confidence: 98%
“…21 As learner engagement has been strongly associated with teaching effectiveness, it is key for educators to maximize engagement with the virtual platform. 22 This work has limitations. Our response rate of 13% is lower than desirable, and increases the risk of unit non-response bias i.e.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, the questionnaire also investigated the learners' level of engagement. Engagement is a complex phenomenon involving both physical and psychological Active learning strategies constructs (Stephenson et al, 2020). It has been defined as the amount of energy learners physically and psychologically invest to stay attentive, involved and motivated (Bernard, 2015;Astin, 1984).…”
Section: Below)mentioning
confidence: 99%
“…It has been defined as the amount of energy learners physically and psychologically invest to stay attentive, involved and motivated (Bernard, 2015; Astin, 1984). Studies have demonstrated that more engaged learners are more satisfied and have better performance concerning course learning objectives (Stephenson et al , 2020; Bernard, 2015; Astin, 1984.) In this study, engagement was measured through the understanding of course content and the level of attention in class (Figures 4 and 5).…”
Section: Assessment and Reflectionsmentioning
confidence: 99%
“…This transition creates questions about effective education, which depends on learner engagement for success. 1 3 Engagement serves as an important and measurable link between instruction and educational outcomes and is defined as focused attention on a specific task. 4 , 5 Accordingly, multiple direct-observation tools to assess learner engagement and behaviors exist for the classroom.…”
Section: Introductionmentioning
confidence: 99%